Exploring Migration as a Climate Change Adaptation Strategy for Agro-pastoralists in Kasulu District: Benefits and Challenges - I. Mwasha, Saumu (Tanzania Journal for Population studies and Development, 2024)
Migration is acknowledged, promoted and widely regarded as one of the adaptation strategies to environmental change in different parts of Africa. However, its benefits and challenges have not been contextually examined and exhaustively analysed. This study employed the push and pull migration theory to investigate opportunities and challenges that result from migration to understand its strengths and weaknesses, and how its implications are linked to issues of migrants’ climate change adaptations in Kasulu District, Tanzania. Purposive sampling was used to select the study district, participants for focus group discussion, and key informants. Observation, key informant interviews and six separate FGDs were conducted to both agro-pastoralists and farmers. The findings demonstrate that agro-pastoralists exploited opportunities in the places of destination through asset accumulation and by performing different livelihood activities. However, in pursuit of their livelihoods they also contributed to resource degradation and conflicts with local farmers; which were a result of the migrants’ inappropriate integration in the host society, and were influenced by different actors, including individuals from both host and migrant communities, as well as institutions in host societies. All this challenges the notion that agro-pastoralists migration is an effective form of adaptation to environmental change in general, and climate change in particular. Migration has a potential of being an effective climate change adaptation strategy; however, it requires the government to coordinate the movement and regulate its activities to reduce conflicts with host communities, as well as resource degradation.